The Influence of Distributive Justice Organizational Culture Job Satisfaction on Affective Commitment in BKAD Employees of Kulon Progo District - Nooria Kuncoro Wijayanti; Prayekti; Kusuma Chandra Kirana (Jurnal Ekonomi Dan Bisnis, 2023)
This research was conducted with the aim of knowing the effect of distributive justice, organizational culture, job satisfaction on affective commitment. The method used in this research is to use quantitative methods. Data collection techniques in this study used a questionnaire method. The population in this study were employees of the Badan Keuangan dan Aset Daerah (BKAD) of Kulon Progo Regency. The sampling technique used a non-probability model with a total sample of 57 employees of the Badan Keuangan dan Aset Daerah (BKAD) of Kulon Progo Regency. From the T test, the results of distributive justice (X1) have a significant effect on affective commitment (Y) with a sig. of 0.004 <0.05. Organizational culture (X2) has a significant effect on employee performance (Y) with a sig. of 0.000 < 0.05. and job satisfaction (X3) has a significant effect on affective commitment (Y) with a sig. of 0.009 <0.05. Keywords: Distributive justice, organizational culture, job satisfaction, affective commitment